Investigation into the effects of high-Z nano materials in proton therapy. (25th May 2016) - Ahmad, R; Royle, G; Lourenço, A; Schwarz, M; Fracchiolla, F; Ricketts, K
Abstract: High-Z nano materials have been previously shown to increase the amount of dose deposition within the tumour due to an increase in secondary electrons. This study evaluates the effects of high-Z nano materials in combination with protons, and the impact of proton energy, nanoparticle material and concentration. These effects were studied in silico through Monte Carlo simulation and experimentally through a phantom study, with particular attention to macroscale changes to the Bragg peak in the presence of nanoparticles. Three nanoparticle materials were simulated (gold, silver and platinum) at three concentrations (0.01, 0.1 and 6.5 mg ml −1 ) at two clinical proton energies (60 and 226 MeV). Simulations were verified experimentally using Gafchromic film measurements of gold nanoparticles suspended in water at two available high concentrations (5.5 mg ml −1 and 1.1 mg ml −1 ). A significant change to Bragg peak features was evident, where at 226 MeV and 6.5 mg ml −1, simulations of gold showed a 4.7 mm longitudinal shift of the distal edge and experimentally at 5.5 mg ml −1, a shift of 2.2 mm. Simulations showed this effect to be material dependent, where platinum having the highest physical density caused the greatest shift with increasing concentration. A dose enhancement of 6% ± 0.05 and 5% ± 0.15 (60 MeV and 226 MeV, respectively) was evident with gold at 6.5 mg ml −1 to water alone, compared to the 21% ± 0.53 observed experimentally as dose to film with 5.5 mg ml −1 of gold nanoparticles suspended in water at 226 MeV. The introduction of nanoparticles has strong potential to enhance dose in proton therapy, however the changes to the Bragg peak distribution that occur with high concentrations need to be accounted for to ensure tumour coverage.